Altered Metabolism and Newborn Screening Using Tandem Mass Spectrometry: Lessons Learned from the Bench to Bedside - H. Chace; R. Spitzer, Alan (Current Pharmaceutical Biotechnology, 2011)
The use of tandem mass spectrometry (MS/MS) for screening of inherited metabolic disease in newborns has afforded many unique opportunities in the understanding of the benefits early their early detection, diagnosis and treatment. From the standpoint of the laboratory and modern analytical methods, the use of MS based analysis demonstrated that a multiple metabolite-multiple disease screen-one method approach expanded screening significantly. MS/MS and newborn screening has served as a model of one type of approach in preventative health care that has shown proven benefits. It has been nearly 20 years since the introduction of MS/MS analysis of dried blood spots from newborns. There have been many lessons learned in both the analytical approach as well as follow-up at the bedside. These lessons can be applied to future applications of MS/MS in newborn screening as well as other areas of metabolism and metabolic profiles such as that from acquired disease, environmental disease and other factors such as nutrition and age. The use of a highly specific, sensitive and multiplex platform such as MS/MS will continue to grow and experience in the newborn screening application will insure this outcome.
Keywords: mass spectrometry